Cerebrospinal fluid penetration of tigecycline - Carlo Pallotto; Maurizio Fiorio; Antonio D'Avolio; Alessio Sgrelli; Franco Baldelli; Giovanni Di Perri; Giuseppe Vittorio Luigi De Socio (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Today very little is known about tigecycline penetration into cerebrospinal fluid (CSF).